Evaluation of scenarios for improving the collection system for a milk factory in Ethiopia: Combination of a simple model, economic analysis, and the effect on GHG emissions - Dijkink, Bert; Axmann, Heike (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This study combined a quality models with locally realistic logistic scenarios as a practical way to assess the feasibility of various options. The analysis addresses four common criteria when evaluating the implementation of these scenarios: (1) the effect on the potential yield of good quality milk; (2) the cost-effectiveness; (3) the effect on total greenhouse gas (GHG) emissions; and (4) the technical feasibility and practical and economic consequences. This way of comparing scenarios can hopefully contribute to better implementation of interventions that can genuinely improve the lives of smallholder farmers and stimulate economic growth for them.